Tìm x :3x-28=x+36
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(-45:5.\left(-3-2x\right)=3\)
\(-9.\left(-3-2x\right)=3\)
\(-3-2x=\left(3:-9\right)\)
\(-3-2x=\dfrac{-1}{3}\)
\(-2x=-3-\dfrac{1}{3}\)
-2x=\(\dfrac{-10}{3}\)
\(x=\dfrac{-10}{3}:-2\)
\(x=\dfrac{5}{3}\)
b)
3x - 28 = x + 36
<=> 3x - x = 36 + 28
<=> 2x = 64
<=> x = 32
Vậy x = 32
c)
(-12)2.x = 56 + 10.13.x
144.x = 56 + 130.x
144x – 130 x = 56
14x = 56
x = 56: 14
x = 4
Vậy x = 4
a.
\(10-2\left(4-3x\right)=-4\)
\(\Leftrightarrow2\left(4-3x\right)=10+4\)
\(\Leftrightarrow2\left(4-3x\right)=14\)
\(\Leftrightarrow4-3x=7\)
\(\Leftrightarrow3x=-3\)
\(\Leftrightarrow x=-1\)
b.
\(-12+3\left(-x+7\right)=-18\)
\(\Leftrightarrow3\left(-x+7\right)=-18+12=-6\)
\(\Leftrightarrow-x+7=-6:3=-2\)
\(\Leftrightarrow x=9\)
c.
\(-45:5.\left(-3-2x\right)=3\)
\(\Leftrightarrow-9.\left(-3-2x\right)=3\)
\(\Leftrightarrow-3-2x=-\dfrac{1}{3}\)
\(\Leftrightarrow2x=-\dfrac{8}{3}\)
\(\Leftrightarrow x=-\dfrac{4}{3}\notin Z\left(loại\right)\)
Câu này em ghi sai đề?
d.
\(3x-28=x+36\)
\(\Leftrightarrow2x=28+36\)
\(\Leftrightarrow2x=64\)
\(\Leftrightarrow x=32\)
e.
\(\left(-12\right)^2.x=56+10.13x\)
\(\Leftrightarrow144x=56+130x\)
\(\Leftrightarrow144x-130x=56\)
\(\Leftrightarrow14x=56\)
\(\Leftrightarrow x=4\)
3x-28=x+36
=>3x-x=28+36
=>2x=64
=>\(x=\dfrac{64}{2}=32\)
a) \(58+7x=100\)
\(=>7x=100-58\)
\(=>7x=42\)
\(=>x=42:7\)
\(=>x=6\)
b) \(3x-7=28\)
\(=>3x=28+7\)
\(=>3x=35\)
\(=>x=35:3\)
\(=>x=\dfrac{35}{3}\)
c) \(x-56:4=16\)
\(=>x-14=16\)
\(=>x=16+14\)
\(=>x=30\)
d) \(101+\left(36-4x\right)=105\)
\(=>36-4x=105-101\)
\(=>36-4x=4\)
\(=>4x=36-4\)
\(=>4x=32\)
\(=>x=32:4\)
\(=>x=8\)
e) \(\left(x-12\right):12=12\)
\(=>x-12=12.12\)
\(=>x-12=144\)
\(=>x=144-12\)
\(=>x=132\)
f) \(\left(3x-2^4\right).7^3=2.7^4\)
\(=>3x-2^4=2.7^4:7^3\)
\(=>3x-16=2.7=14\)
\(=>3x=14+16\)
\(=>3x=30\)
\(=>x=30:3\)
\(=>x=10\)
i) \(\left(10+2x\right).4^{2011}=4^{2013}\)
\(=>10+2x=4^{2013}:4^{2011}\)
\(=>10+2x=4^2=16\)
\(=>2x=16-10\)
\(=>2x=6\)
\(=>x=6:2\)
\(=>x=3\)
\(#WendyDang\)
X + 7 = 36
X = 36 − 7
X = 29
19 + x = 58
X = 58 − 19
X = 39
X + 28 = 75
X = 75 − 28
X = 47
a: \(\Leftrightarrow\dfrac{3x-2}{\left(x-2\right)\left(x-10\right)}-\dfrac{4x+3}{\left(x+8\right)\left(x-2\right)}=\dfrac{8x+11}{\left(x-10\right)\left(x+8\right)}\)
=>(3x-2)(x+8)-(4x+3)(x-10)=(8x+11)(x-2)
=>3x^2+24x-2x-16-4x^2+40x-3x+30=8x^2-16x+11x-22
=>-x^2+59x+14-8x^2+5x+22=0
=>-9x^2+54x+36=0
=>x^2-6x-4=0
=>\(x=3\pm\sqrt{13}\)
b: \(\Leftrightarrow\dfrac{2x-5}{\left(x+9\right)\left(x-4\right)}-\dfrac{x-6}{\left(x+7\right)\left(x-4\right)}=\dfrac{x+8}{\left(x+9\right)\left(x+7\right)}\)
=>(2x-5)(x+7)-(x-6)(x+9)=(x+8)(x-4)
=>2x^2+14x-5x-35-x^2-9x+6x+54=x^2+4x-32
=>x^2+6x+19=x^2+4x-32
=>2x=-51
=>x=-51/2
\(x\) x 18 = 28 x 3,6 + 36 x 7,2
\(x\) x 18 = 28 x 3,6 + 3,6 x 72
\(x\) x 18 = 3,6 x ( 28 + 72)
\(x\) x 18 = 3,6 x 100
\(x\) x 18 = 360
\(x\) = 360 : 18
\(x\) = 20
\(4x^2-28=0\)
\(\Leftrightarrow4\left(x^2-7\right)=0\)
\(\Leftrightarrow x^2-7=0\)
\(\Leftrightarrow x^2=7\)
\(\Leftrightarrow x=\pm\sqrt{7}\)
3\(x\) - 28 = \(x\) + 36
3\(x\) - \(x\) = 36 + 28
2\(x\) = 64
\(x\) = 64 : 2
\(x\) = 32
3x - 28 = x+36
3x - x = 36+28
2x =64
x=64:2
x=32